Dynamics of Oblate Test Particle under the Influence of Oblate and Radiating Primaries in Elliptic Restricted Three Body Problem - Narayan, A.; Chakraborty, A.; Dewangan, A. (Journal of Informatics and Mathematical Sciences, 2018)
This paper presents a generalized problem of the photogravitational restricted three body, where both the primaries are radiating; in the sense that the eccentricity of the orbits and the oblateness due to both the primaries and infinitesimal are considered. The positions and stability of the equilibrium points of this problem are studied. The stability analysis ensures that, the collinear equilibrium points are unstable in the linear sense while the stability condition for the triangular points is obtained. For illustrative numerical exploration four binary system: Luyten-726, Kruger-60 and Alpha-Centauri are considered, the location and stability of their planar equilibrium points are studied semi-analytically.